2005
DOI: 10.3748/wjg.v11.i42.6650
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection for high-grade dysplasia and intramucosal carcinoma in Barrett’s esophagus: An Italian experience

Abstract: In the medium term, EMR is effective and safe to treat HGD and/or IMC within BE and is a valuable staging method. It could become an alternative to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 37 publications
2
38
0
4
Order By: Relevance
“…These data demonstrated the efficacy of EMR for Barrett's dysplasia and IMC. On the other hand CBE-EMR seems to be associated with more complications [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200]. Rates of bleeding and perforation in large EMRs increased up to 19% and 11% respectively, and appear to be higher than those for ablative modalities [195,198].…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 92%
See 1 more Smart Citation
“…These data demonstrated the efficacy of EMR for Barrett's dysplasia and IMC. On the other hand CBE-EMR seems to be associated with more complications [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200]. Rates of bleeding and perforation in large EMRs increased up to 19% and 11% respectively, and appear to be higher than those for ablative modalities [195,198].…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 92%
“…Therefore, EMR has been accepted method for BE with small and/or raised lesions of HGD or IMC [172]. Independently of endoscopic techniques, the most common complications of EMR are bleeding and esophageal stricture formation, but most of them can be treated successfully by endoscopy [186][187][188][189][190][191][192][193][194][195][196][197][198][199]. Perforation has been reported in 1-2.6% of the patients, but seems to decrease with more experience.…”
Section: Non Ablative Modalities (Endoscopic Resection-emr)mentioning
confidence: 99%
“…Conio et al (109) and Mino-Kenudson et al (110) reported a changed histological diagnosis in 26 and 37%, respectively, of patients with BE undergoing EMR. Studies suggest that EMR may successfully eliminate early ADC with a low complication rate but relapse rates of 25-30% during the first 3 years when used as single therapy in patients with HGD or intramucosal ADC (111).…”
Section: Endoscopic Mucosal Resection (Emr)mentioning
confidence: 99%
“…Unlike other ablative methods, EMR permits histological assessment of the whole lesion permitting definition of lateral extent and depth. It alters the pathological staging in BO in 26-37% of patients [Conio et al 2005;Mino-Kenudson et al 2005]. EMR is suitable for short segments of BO, early OA and particularly useful for visible lesions.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%